Proceedings of the 2nd International Workshop on Pattern-Driven Engineering of Interactive Computing Systems 2011
DOI: 10.1145/2018431.2018434
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-based user interface transformation for knowledge sharing applications

Abstract: In this paper we present a pattern-based method for transforming user interfaces of knowledge sharing applications. We highlight a hierarchical pattern language which has been developed in the context of project p.i.t.c.h. (pattern-based interactive tools for improved communication habits in knowledge transfers). On this foundation we use the transformation process of the PaMGIS (Pattern-based Modeling and Generation of Interactive Systems) framework in order to create user interfaces for various contexts of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In [7] it is concluded that it is possible to map the pattern descriptions contained in the previously mentioned pattern collections into PLML compliant formats, however this cannot be done in a fully automated manner.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [7] it is concluded that it is possible to map the pattern descriptions contained in the previously mentioned pattern collections into PLML compliant formats, however this cannot be done in a fully automated manner.…”
Section: Related Workmentioning
confidence: 99%
“…The framework has been continuously improved. Patterns are now available in a modified PLML format and seamless pattern hierarchies can be modeled [7].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Stating a UIP definition is not easily done since a standardization of this term has yet to be reached [7]. What can be assumed is a separation of UIPs between their usage in specification or generation of software, hence the pattern idea for GUI systems found its roots in HCI [8] and now evolves towards automated or generative development [9].…”
Section: Uip Definition and Collectionsmentioning
confidence: 99%
“…There have been attempts to create a unified description scheme with the introduction of PLML (pattern language markup language) in 2003 [10]. Engel, Herdin and Märtin conducted an investigation of common description schemes in [7]. Descriptive UIPs are established as specification elements and supported by the HCI community.…”
Section: Plmlmentioning
confidence: 99%